Peran Penting Orang Tua dalam Peningkatan Kualitas Pendidikan Dalam Pembelajaran Daring bagi Siswa Tingkat Sd Di Masa Pandemi Covid-19 - Purwaning Budi Lestari; Tri Asih Wahyu Hartati; Titik Wijayanti (Universitas Insan Budi Utomo, 2023)
The role of parents is very important in online learning during the Covid-19 pandemic. Online learning forces parents to use technology, sudden changes in the learning process due to the COVID-19 virus often make teachers (educators), students, and parents unable to accept the situation. The purpose of this research is to describe the role of parents in improving the quality of education in online learning for elementary school students during the Covid-19 pandemic. The method used is literature and qualitative studies. The results of the research show that based on a literature study, the implementation of online learning in elementary school can be carried out quite well if there is cooperation between teachers, students and parents in studying at home. Meanwhile, based on the results of interviews, there are many obstacles experienced by parents in online learning. One solution is through the implementation of interactive videos in helping online learning activities at home with parents. The conclusion is to increase the role of parents in implementing online learning to improve the quality of learning during the Covid-19 pandemic, there is a need for learning innovations through the implementation of interactive videos.